Two distinctive energy migration pathways of monolayer molecules on metal nanoparticle surfaces - Jiebo Li (Nature Portfolio, 2016)
Energy migrations at metal nanomaterial surfaces are fundamentally important to heterogeneous reactions. Here, the authors employ ultrafast vibrational spectroscopy to show two distinctive energy migration pathways of monolayer adsorbate molecules on differently sized metal nanoparticle surfaces.